Cross-border spillover effects of macroprudential policies: A conceptual framework - Christoffer Kok Sørensen; Dennis Reinhardt (European Central Bank (ECB), 2020)
Due to the international dimension of the financial sector within the EU and beyond, domestically oriented macroprudential policies have the potential to create material cross-border spillover effects. This occasional paper provides a detailed overview of the academic and empirical literature on cross-border effects of macroprudential policies. It also summarises a stocktaking exercise, conducted by a task force of the ESCB's Financial Stability Committee (FSC), on existing national approaches within the EU for assessing and monitoring such cross-border spillover effects. The paper accompanies an FSC report presenting a framework to be used by macroprudential authorities when assessing cross-border spillover effects induced by enacted or planned policy measures.
Keywords: E42; E58; F36; G21; 330; European Central Bank; banking union; financial stability; systemic risks; macroprudential policies; cross-border spillovers